An investigation into the translation of metaphorical expressions of love in “Truyện Kiều” by Nguyen Du and its English version by michael counsel - Huỳnh Thị Kim Hằng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis mainly focuses on analyzing the metaphorical expressions of love in “Truyện Kiều” by Nguyen Du and its English version by Michael Counsel. The analysis, discussion and comments have been made to finding out the differences and similarities in the language of metaphorical expressions of love in this work. The descriptive and contrastive methods are used in combination with the qualitative and quantitative approaches in order to help the researcher achieve the aims and objectives proposed. The data for analysis were taken from the masterpiece with 11 conceptual domains underlying 225 spatial expressions and 25 temporal ones. At the result, we have figured out 75 conceptual metaphors of love in Truyện Kiều by Nguyen Du and 40 conceptual metaphors of love in English version by Michael Counsel. The study has pointed out the similarities and the differences the conceptual metaphorical expression of love between the original version and its version in English. Besides giving an in-depth understanding of conceptual metaphors of love in the work, the research is carried out in the hope of adding the voice to the variety of conceptual metaphors. Moreover, making a contribution to the variety of conceptual metaphors is also our desire. In addition, implications of the thesis could be a useful reference for those who are interested in teaching and learning conceptual metaphors.